An efficient method for the construction of functionalized DNA bearing amino acid groups through cross-coupling reactions of nucleoside triphosphates followed by primer extension or PCR - Čapek, Petr; Macíčková Cahová, Hana; Pohl, Radek; Hocek, Michal; Gloeckner, Christian; Marx, Andreas (Chemistry, 2007)
Single-step aqueous cross-coupling reactions of nucleobase-halogenated 2'-deoxynucleosides (8-bromo-2'-deoxyadenosine, 7-iodo-7-deaza-2'-deoxyadenosine, or 5-iodo-2'-deoxy-uridine) or their 5'-triphosphates with 4-boronophenylalanine or 4-ethynylphenylalanine have been developed and used for efficient synthesis of modified 2'-deoxynucleoside triphosphates (dNTPs) bearing amino acid groups. These dNTPs were then tested as substrates for DNA polymerases for construction of functionalized DNA through primer extension and PCR. While 8-substituted adenosine triphosphates were poor substrates for DNA polymerases, the corresponding 7-substituted 7-deazaadenine and 5-substituted uracil nucleotides were efficiently incorporated in place of dATP or dTTP, respectively, by Pwo (Pyrococcus woesei) DNA polymerase. Nucleotides bearing the amino acid connected through the less bulky acetylene linker were incorporated more efficiently than those directly linked through a more bulky phenylene group. In addition, combinations of modified dATPs and dTTPs were incorporated by Pwo polymerase. Novel functionalized DNA duplexes bearing amino acid moieties were prepared by this two-step approach. PCR can be used for amplification of duplexes bearing large number of modifications, while primer extension is suitable for introduction of just one or several modifications in a single DNA strand.
Keywords: financování organizované; Base Sequence; polymerázová řetězová reakce; nukleotidy; Polymerase Chain Reaction; Molecular Structure; Nucleosides; DNA; Molecular Sequence Data; DNA primery; nukleosidy; Financing, Organized; molekulární struktura; Nucleotides; DNA-dependentní DNA-polymerasy; molekulární sekvence - údaje; Circular Dichroism; sekvence nukleotidů; DNA-Directed DNA Polymerase; DNA Primers; Amino Acids; aminokyseliny; cirkulární dichroismus